PENGARUH KUALITAS PENGUNGKAPAN INFORMASI TERHADAP HUBUNGAN ANTARA PENERAPAN CORPORATE GOVERNANCE DENGAN KINERJA PERUSAHAAN DI BURSA EFEK JAKARTA - Erna Hidayah (Jurnal Akuntansi dan Auditing Indonesia, 2008)
Good corporate governance is a principle that guide and control companies to achieve balance between companies' strength and authority in reporting to shareholders and stakeholders. Companies that have applied corporate governance and have better disclosure quality, will be more trustworthy to creditors and investors and therefore their share are more liquid and share price will be increased. Overall, the market performance will be better.        This research will try to prove whether application of good corporate governance will influence the market performance, and whether information disclosure quality is the moderating variable for those two variables.        The disclosure quality is measured by using compulsory disclosure index and information reporting punctuality. Meanwhile, corporate governance application is measured by using CGPI value of IICG survey results, and companies' performance is measured by using Tobin's Q value. Statistical method used in this research is linear regression and interaction test. Research sample is companies listed in Jakarta Stock Exchange and participated in the survey done by IICG in 2001-2004.        Based on the hypotheses test, it can be concluded that the companies’ market performance is not affected by Corporate Governance application. Moreover, it can be proved that compulsory disclosure index and information reporting punctuality are not the moderating variable that can influence the relationship between corporate governance application and the companies’ performance.        This demonstrates that Indonesian market has not paid much attention to the application of corporate governance, or, there is a possibility that the market’s respond to the information of corporate governance application does not happen instantly or in short term (next 1 year), but it takes longer time and more information on corporate governance application in several years.Key words: corporate governance, compulsory disclosure index, information reporting punctuality, Tobin’s Q value